P-318 Nox1 and Duox2 Overexpression: New Insights in TLR4-mediated Susceptibility to Inflammation and Tumorigenesis. (February 2017) - Burgueno, Juan; Landau, Kevin; Pierre, Leconte; Kalser, Sophie; Santander, Ana; Fernández, Irina; Abreu, Maria
Abstract : Background: We have previously shown that toll-like receptor (TLR) 4 increases susceptibility to intestinal inflammation and neoplasia, and induces intestinal epithelial cell (IEC) proliferation via activation of different signaling pathways. NADPH oxidase (Nox) 1 and dual oxidase (Duox) 2 can act as downstream targets of TLR4, producing radical oxygen species after lipopolysaccharide (LPS) challenge. We hypothesized that TLR4 signaling differentially regulates Nox1 and Duox2 expression in the intestine under different pathophysiologic conditions. Methods: Duodenum, ileum and colon were collected from villin-TLR4 mice, which have constitutive activation of epithelial TLR4, and their wild-type (WT) littermates. Full-thickness samples, spontaneous duodenal adenomas (in villin-TLR4 mice) and isolated IEC were processed for quantitative PCR determinations. Using previously published Gene Expression Omnibus (GEO) datasets from NCBI (http://www.ncbi.nlm.nih.gov/gds ), dataset searches containing keywords "inflammatory bowel disease" (IBD), "colon cancer" and "colorectal cancer" were performed. The Affymetrix Expression Console (EC) (build 1.4.1.46) and the Affymetrix Transcriptome Analysis Console 3.0 (TAC) software were used to obtain analysis of variance and false discovery rate P -values for Nox1, Duox2 and TLR4 gene expression probe reads. Results: mRNA expression of Nox1 and Duox2 in full-thickness samples gradually increased in a proximal to distal fashion in the different bowel sections of WT mice. Villin-TLR4 mice had Nox1 expression up-regulated by 147-fold in duodenum, and 9-fold in ileum and colon, while Duox2 was overexpressed by 34-fold in duodenum and 5-fold in ileum and colon (as compared to WT mice expression in the same section). In spontaneous adenomas, overexpression of Nox1 and Duox2 transcript levels reached 643- and 150-fold differences when compared to WT duodenum expression (4.5-fold difference for both genes when compared to villin-TLR4 duodenum expression). Most of this Nox1 and Duox2 up-regulation occurred in IEC, as villin-TLR4 IEC displayed Nox1 increases of 589-, 719- and 12-fold, and Duox2 increases of 83-, 6- and 7.6-fold in the different sections, respectively, when compared to WT littermate IEC. Additional computational analysis corroborated our observations in human neoplastic tissue, and extended them to IBD-related conditions. Indeed, in GEO dataset GSE8671, overexpression of TLR4 was accompanied by significant up-regulation of Nox1 and Duox2 in colorectal adenomas when compared to healthy colon. Finally, in GSE10616, up-regulation of TLR4/Duox2 or TLR4/Nox1/Duox2 was observed in ulcerative colitis and Crohn's disease, respectively, as compared to healthy controls. Conclusions: Our preliminary data suggest that TLR4 activation and overexpression induce Nox1 and Duox2 mRNA synthesis. These genes, which are up-regulated during inflammation and neoplasia, may be critically involved in bacterial-mediated susceptibility to these disorders in a TLR4-dependent fashion.